Transformation parameters between UCS-2000 and WGS-84 - Novikova, Elena; Palamar, Alena; Makhonko, Svetlana; Barna, Alexander; Privalova, Olga (Geodesy and Cartography, 2018)
According to the Order of the Ministry of Agrarian Policy of Ukraine, published in 2016, about the procedure for using the national coordinate system UCS-2000, this was the first time officially presented parameters of the Helmert transformation from the UCS-2000 system to the ITRF-2000 system. However, all software products are used for communication between various coordinate systems as the main coordinate system, WGS-84. The Helmert transformation parameters between the UCS-2000 and WGS-84 systems are found for the new realization of WGS-84 (G1762) based on GPS data and the old realization of the WGS-84, based on the US Satellite Navigation System, known as DOPPLER Transit. It is shown that the use of the transformation parameters of the old realization WGS-84 for the processing of present GPS measurements will result in a systematic error of the order of 0.6 m. Obtained transformation parameters can be used as the first approximation to obtain accurate Helmert transformations based on GPS measurements at points with known coordinates in the UCS-2000 system. The described procedure for determining the parameters will be especially useful in the case when a more accurate connection will be established between the systems ITRFyy and WGS-84, than the current one.